Rethinking international organization : deregulation and global governance - Emadi-Coffin, Barbara, 1951- (Routledge advances in international political economy, 2003)
The increasing interaction of multinational corporations, international organizations and transnational interest groups, such as Greenpeace and Amnesty International are analyzed in relation to the global political economy.